2009
DOI: 10.1017/s1368980009990851
|View full text |Cite
|
Sign up to set email alerts
|

Information design to promote better nutrition among pantry clients: four methods of formative evaluation

Abstract: Objective: To demonstrate the use of four different qualitative methods in creating content, including text and graphic design for print interventions to support better nutrition in low-income households that rely on charitable pantries. Design: Four methods were used for measuring household cooks' responses to the content and design of recipes and food-use tips especially designed for lowincome households: (i) focus groups with pantry clients; (ii) questionnaires administered at sites where the Women, Infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Others have reported that providing a user‐friendly recipe to pantry clients can impact behavior change related to eating more healthfully (Evans et al. ; Keller‐Olaman, Edwards, & Elliott, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Others have reported that providing a user‐friendly recipe to pantry clients can impact behavior change related to eating more healthfully (Evans et al. ; Keller‐Olaman, Edwards, & Elliott, ).…”
Section: Discussionmentioning
confidence: 99%
“…That is, recipes should: (1) avoid ingredients that clients of pantries do not have at home, (2) make sparing use of salt, sugar, and refined carbohydrates, (3) use a colored picture on the recipe card (Evans et al. ), and (4) accommodate limited skills of literacy and numeracy (Rogers, Ratzan, & Payne, ). Based on the information design research of Evans et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations